2019
DOI: 10.1016/j.jfda.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of babchi essential oil into microsponges: Physicochemical properties, cytotoxic evaluation and anti-microbial activity

Abstract: Babchi essential oil (BEO) is a valuable essential oil reported to possess a variety of biological activities such as antitumor, anti inflammatory, immunomodulatory, antioxidant, antifungal and antibacterial properties. Due to its anti-microbial properties, this oil possesses an immense potential for the treatment of dermatological disorders. Further, it has minimal tendency to develop resistance, a common issue with most of the antibiotics. However, its highly viscous nature and poor stability in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…The in vitro cytotoxicity of EtOAc fraction of D. moldavica L. ethanol extract was investigated using human epidermal keratinocyte (HaCaT) cell line as described previously by Wadhwa et al. (Wadhwa et al., 2019). HaCaT cells were cultivated in Dulbecco’s modified Eagle’s medium (DMEM) medium supplemented in 10% fetal bovine serum (FBS, Thermo Fisher Scientific, MA, USA), streptomycin (100 μg/ml, Thermo Fisher Scientific, MA, USA), and penicillin (100 IU/ml, AppliChem GmbH, Darmstadt, Germany) in a humidified atmosphere containing 5% CO 2 at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro cytotoxicity of EtOAc fraction of D. moldavica L. ethanol extract was investigated using human epidermal keratinocyte (HaCaT) cell line as described previously by Wadhwa et al. (Wadhwa et al., 2019). HaCaT cells were cultivated in Dulbecco’s modified Eagle’s medium (DMEM) medium supplemented in 10% fetal bovine serum (FBS, Thermo Fisher Scientific, MA, USA), streptomycin (100 μg/ml, Thermo Fisher Scientific, MA, USA), and penicillin (100 IU/ml, AppliChem GmbH, Darmstadt, Germany) in a humidified atmosphere containing 5% CO 2 at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…[112,113] Their features have been found to enhance the loading ability and stability of active components, and reduce local irritation, meaning that this technique is used in cosmetic and dermatological products. Essential oils with antibacterial activity [114,115] and drugs [116][117][118] have shown interesting results in topical delivery, when loaded into microsponges, over different wound infected models. Other potential topical applications are ocular use [119], and antifungal vaginal formulations [120].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…In terms of antiinflammatory activity, Wijayadi and Rusli [119] revealed that encapsulating lime EO into chitosan nanoparticles improved the inhibitory activity of the EO against Propionibacterium acnes with minimal side effects. Wadhwa et al [96] has formulated Babchi EO encapsulated in ethyl cellulose microsponges for dermatological treatment. e formulation effectively inhibited P. aeruginosa, S. aureus, and E. coli.…”
Section: Pharmaceutical Sectormentioning
confidence: 99%